PERAN KEPEMIMPINAN UNTUK MEMOTIVASI DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT SUNLIFE CABANG MEDAN - Santri Yani Zainta; Rahma Wulan Suci; Seri Handayani; Zainarti, Zainarti (Pusat Riset dan Inovasi Nasional, 2022)
The Role of Leadership in Improving Employee Performance is very important in improving employee performance in an organization or company. Everything related to the progress and success of an organization can only be carried out by the intervention or ideas of a leader. The role of a leader can be known through his success in achieving organizational goals.Work motivation: basically motivation is more focused on how to arouse the desire in an employee to want to work productively for the sake of create what has been set. Supardi and Anwar (2004:47) say that 'Motivation is a state in a person's personality that drives an individual's desire to carry out certain activities to achieve goals.Performance: is the result of work achieved by a person based on the responsibilities given to him good performance is important for the company and the employees themselves. Increased employee performance can be used as a consideration for companies to develop human resources and by increasing employee performance, it will also have an impact on company stability in the process of achieving set goals. Good performance achievement must be supported by employees who have high work motivation and discipline to improve the abilities of these employees. So that employees will be able to work according to the skills and abilities they have and produce satisfactory performance for the company. For this reason, work motivation and work discipline have a close bond with the performance of employees in a company or organization.